Remission in patients with active rheumatoid arthritis by tocilizumab treatment in routine clinical practice: results from 3 years of prospectively registered data. Issue 2 (March 2014) - Nakashima, Yasuharu; Kondo, Masakazu; Fukuda, Takaaki; Harada, Hiroshi; Horiuchi, Takahiko; Ishinishi, Takashi; Jojima, Hiroshi; Kuroda, Koji; Miyahara, Hisaaki; Maekawa, Masayuki; Nishizaka, Hiroaki; Nagamine, Ryuji; et al.
Abstract Objectives. This study aimed to evaluate the remission in rheumatoid arthritis (RA) patients treated with tocilizumab (TCZ), based on prospectively registered data in clinical practice. Methods. We studied 114 consecutive RA patients treated with TCZ for an average of 3.5 years. Remission was evaluated by using the EULAR criteria and the new ACR/EULAR Boolean-based criteria. Results. Among 114 patients (average age 52.2 years; average disease duration 10.6 years), 76 (67 %) had previously received anti-TNF biologics. Mean baseline DAS28-ESR of 5.4 and improved to 2.4 at 36 months. Overall, DAS28-ESR <2.6 was attained by 66.7 %, while ACR/EULAR remission was attained by 35.1 %. ACR/EULAR remission rate was significantly higher in the patients who were biologics-naïve and had good response at the first month. Among 23 patients who completed the treatment for 3 years and had ACR/EULAR remission at 1 year, 15 (65 %) remained in the remission and 16 (70 %) had a DAS28-ESR <2.6 at the final follow-up. The retention rate at 36 months was 68.2 %. Conclusions. In patients with RA, TCZ is highly effective for both biologics-naïve patients and patients previously exposed to biologics, achieving a high remission rate and drug continuation rate (68.2 %) in clinical practice.